High-yield hydrogen production from glucose by supercritical water gasification without added catalyst - Susanti, Ratna F.; Dianningrum, Laras W.; Yum, Taewoo; Kim, Yunje; Lee, Byung Gwon; Kim, Jaehoon (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
Continuous supercritical water gasification of glucose is investigated with a recently developed updraft gasification apparatus under various conditions: temperatures of 600 -767 degrees C, residence times of 15-60 s, glucose concentrations of 1.8-15 wt% and without added a catalyst. The experimental gas yields are compared with predicted values at equilibrium that are estimated via Gibbs free energy minimization. Total gas yields and hydrogen gas yield increase with temperature. At 740 degrees C and 1.8 wt%, hydrogen gas yields become very high (10.5-11.2 mol/mol glucose). The hydrogen gas yields do not vary significantly with different residence times. The hydrogen gas yield decreases to 5.7 mol/mol glucose at 15 wt%, a value very close to the predicted value (6.3 mol/mol glucose). Only acetic acid is detected in the liquid effluents at temperatures above 740 degrees C, while 42 products are detected at 600 degrees C. The highest hydrogen gas yield obtained in this study is 11.5 mol/mol glucose at 25 MPa, 767 degrees C, and 1.8 wt%, for 60 s; this value is very close to the theoretical equilibrium hydrogen yield of 11.9 mol/mol glucose. Under these conditions, the carbon efficiency is very high (91%) and total organic carbon (TOC) in the liquid product is very low (23 ppm), indicating that glucose is almost completely converted to gaseous products. Comparison with other work under similar operating conditions shows that the current reactor is capable of attaining higher hydrogen gas yields at temperatures above 650 degrees C. Possible explanations for the higher hydrogen gas yields are presented. Crown Copyright (C) 2012, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: HOT-COMPRESSED WATER; BIOMASS GASIFICATION; HYDROTHERMAL GASIFICATION; THERMODYNAMIC ANALYSIS; NICKEL-CATALYST; MODEL COMPOUNDS; KEY COMPOUNDS; OXIDATION; CONVERSION; KINETICS